The Implementation of Solar Charge Controller For Uninterruptible Power Supply - Rosli, Ahmad Mustaqim; Mohd Jamail, Nor Akmal; Kamarudin, Qamarul Ezani (Evolution in Electrical and Electronic Engineering, 2023)
Solar charge controller (SCC) and uninterruptible power supply (UPS) are different types of devices. SCC is an important element in the solar electric panel system while UPS is a device that allows any load to keep functioning for at least a short time when there is a power failure. The solar charge controller is used to regulate the voltage to ensure the battery is safe and can be used for the long term. Without SCC, the battery may be damaged since the SCC function is to control the current from overcharging or draining the battery. Overcharging and severe draining dramatically shorten the lifespan of batteries. This project was to implement the UPS system for the SCC by using the inverter with 1000 W to change the direct current (DC) to alternating current (AC). The 12 V PV solar panel was used in this project to harvest the solar energy and convert it to electrical energy. The battery used in this project is 12 V with 1.2 Ah capacity. The NE556 was used to control the working function of the circuit and the operation of the logic of the circuit while in the simulation using IC 555 because in the Proteus software library, the NE556 was not available but the function was still the same since two IC 555 was equal to one NE556. The result during charging and discharging shows that the SCC can protect the battery from overcharging when the maximum voltage for the battery is around 13.20 V and the current is 0 A while, for the discharging the data taken from the battery and load. When the minimum voltage of the battery reaches around 11.6 V it shows the current load 0 A. In conclusion, this project was accomplished, and the UPS system worked very well when connected to the SCC system.